THE USE OF SAGO RESIDUE FERMENTATION AGAINST PERFORMANS SHEEP - M T Siagian; M Tafsin; S Umar; E Mirwandhono; A H Daulay (Jurnal Peternakan Integratif, 2017)
Abstract. This study objective was to examine the quality of sago residue fermented with Effective microorganism 4 (EM4) on merino sheep performance. This research was conducted in Kec. Binjai City of North Sumatra. This research has been conducted for 3 months starting from October until December 2016 using 20 sheep merino with initial weight of 18.30 ± 1.16 kg. The design used in this study was a complete randomized design (RAL) with 4 treatments and 5 replications. This treatment consists of P0 (non-fermented sago residue 40%); P1 (20% sago residue of fermented + 20% non fermented sago residue); P2 ("30% fermented sago residue + 10% non fermented sago residue) P3 (40% sago residue fermented). The results showed tht the dispersion of sago residue fermented EM4 give significant effect (P <0,05) to feed consumption, PBB and feed conversion. Added body weight and feed conversion. The mean respectively for feed consumption (g / head / day) in the treatment arrangement P0, P1, P2, P3 was 470.0; 539,7; 565.0; And 632.2. The average weight gain (g / head / day) was 59.6; 76.1; 99.2; 111.7 and the feed conversion rate was 11.6; 9,13; 6.65; And 5.78. The conclusion of this study is that the use of sago residue fermented EM4 to 40% level in the ration has a positive effect in increasing the body weight, feed consumption and decreasing the value of feed conversion to sheep. Keywords : sago, residue, fermentation